RAPID DETECTION OF RAT MEAT ADULTERATION IN BEEF SAUSAGES USING FTIR‑ATR SPECTROSCOPY AND CHEMOMETRICS FOR HALAL AUTHENTICATION - LESTARI, DWI; SYAMSUL, EKA SISWANTO; WIRNAWATI; SYAFRI, SURYATI; SYOFYAN, SYOFYAN; ROHMAN, ABDUL; YULIANA, NANCY DEWI; ABU BAKAR, NOR KARTINI BT.; HAMIDI, DACHRIYANUS (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of this study was to employ Fourier Transform Infrared-Attenuated Total Reflectance (FTIR‑ATR) spectroscopy in combination with chemometrics for the analysis of rat meat adulteration in beef sausages. Methods: Lipid components in sausages were extracted using three extraction methods, namely Bligh and Dyer, Folch, and Soxhlet methods. The lipid components extracted were then analysed using FTIR‑ATR spectroscopy, and their spectra obtained were used as variables during chemometrics modeling. Samples were prepared by mixing beef with adulterant of rat meat in the concentration range of 0-100% of rat meat. Each sample was scanned using FTIR-Attenuated Total Reflectance (ATR) spectroscopy in three replicates at 4000-650 cm-1 wavenumber region. Results: The absorbance values at wavenumbers regions of 3100-700 cm-1 were used to discriminate lipid components extracted by the Bligh Dyer, Folch, and Soxhlet Method with an accuracy level of 100%. The prediction of rat sausages was successfully determined using multivariate calibrations of Partial Least Square (PLS) and Principle Component Regression (PCR) using optimised conditions. Conclusion: FTIR-ATR spectroscopy coupled with chemometrics is a rapid and accurate method for detecting and quantifying rat meat in beef sausages for halal authentication.